The impact of water supply reductions on San Joaquin Valley agriculture during the 1986-1992 drought - Dale, Larry L.; Dixon, Lloyd S.; Rand Corporation; United States. Environmental Protection Agency (Santa Monica, CA : RAND, 1998)
In late 1994, California adopted more-stringent water quality standards for the San Francisco Bay/Delta and the San Joaquin and Sacramento River System and is deciding how the water-use reductions necessary to meet these goals should be split between agricultural and urban users. This report attempts to improve understanding of the likely effects of water supply reductions on agriculture. It examines economic theory, past empirical work, new data on the response of San Joaquin Valley farmers to water supply cutbacks during the 1986-1992 drought, and two models that are commonly used to predict the effects of water supply reductions. The report supplies up-to-date information on the effects of water supply reductions on agriculture, which will allow policymakers to review decisions to reallocate water from agriculture to the environment with more accurate information on the costs and benefits.
Includes bibliographical references (p. 71-73).
Also available on the internet via WWW in PDF format.
Keywords: Agriculture -- California -- San Joaquin Valley -- Decision making; Droughts -- California; Water in agriculture -- California -- San Joaquin Valley; Water-supply, Agricultural -- Government policy -- California -- San Joaquin Valley; Water-supply, Agricultural -- California -- San Joaquin Valley